Nonreciprocal superconducting NbSe2 antenna - Zhang, Enze; Xu, Xian; Zou, Yi-Chao; Ai, Linfeng; Dong, Xiang; Huang, Ce; Leng, Pengliang; Liu, Shanshan; Zhang, Yuda; Jia, Zehao; Peng, Xinyue; Zhao, Minhao; et al. (Nature communications, 2020)
The rise of two-dimensional (2D) crystalline superconductors has opened a new frontier of investigating unconventional quantum phenomena in low dimensions. However, despite the enormous advances achieved towards understanding the underlying physics, practical device applications like sensors and detectors using 2D superconductors are still lacking. Here, we demonstrate nonreciprocal antenna devices based on atomically thin NbSe 2 . Reversible nonreciprocal charge transport is unveiled in 2D NbSe 2 through multi-reversal antisymmetric second harmonic magnetoresistance isotherms. Based on this nonreciprocity, our NbSe 2 antenna devices exhibit a reversible nonreciprocal sensitivity to externally alternating current (AC) electromagnetic waves, which is attributed to the vortex flow in asymmetric pinning potentials driven by the AC driving force. More importantly, a successful control of the nonreciprocal sensitivity of the antenna devices has been achieved by applying electromagnetic waves with different frequencies and amplitudes. The device’s response increases with increasing electromagnetic wave amplitude and exhibits prominent broadband sensing from 5 to 900 MHz. Here, the authors observe reversible nonreciprocal charge transport in two-dimensional NbSe 2 , and demonstrate antenna devices exhibiting strong sensitivity to driving AC electromagnetic waves in the superconducting regime.